Strategic Human Resource Management in the AI Era: A Scoping Review on 2024 Adaptation Strategies - Rahmawati, Andi; Rahmat, Muhammad Rijal Alim (PT. Maju Malaqbi Makkarana, 2024)
The era of artificial intelligence (AI) has brought significant changes in Strategic Human Resource Management (SHRM). This study aims to explore organizational adaptation strategies in facing the integration of AI in SHRM after 2024. Using the Scoping Review method, this study identifies key trends, challenges, and best strategies in implementing AI in HR management. The review results show that AI improves efficiency in recruitment, performance evaluation, and employee skills development, but also presents ethical challenges such as algorithmic bias and personal data protection. In addition, companies that are successful in adopting AI implement reskilling and upskilling strategies to ensure workforce readiness. This study provides insights for academics and practitioners in developing HR policies that balance technological efficiency and a human value-based approach.